The Innovation of Brick from Plastic Waste - Norfateha Ayu Ahmad Sapuan,; Nur Athirah Batrisyia Ramli,; Nur Kahirinah Mustapa,; Nor Baizura Hamid, (Multidisciplinary Applied Research and Innovation, 2023)
The use of plastic waste, polyethylene terephthalate (PET) is the main material in producing environmentally friendly bricks. As much as 15% of plastic PET is used in producing this Eco-Brick. Control concrete brick was used as the control sample in this study to determine the workability of this Eco-Brick. The objective of this study is to develop an environmentally friendly structure as an innovation. Thus, Eco-Brick was designed using SketchUp software into Lego shapes as a new innovation in structural work. Furthermore, tests of density, water absorption, and compressive strength were conducted on control concrete brick and Eco-Brick. This experiment was conducted to compare the best results with previous research papers and the American Testing and Materials Association (ASTM). The results for the density test for control concrete bricks were 2791.7 kg/m3, while type T was 2052.1 kg/m3 and type R was 1958.4 kg/m3, respectively. For the water absorption tests of control concrete bricks, type T and type R, the results were 2.83%, 3.23%, and 1.62%. The compressive strength values for control concrete bricks, type T, and type R bricks were 425.4 MPa, 440.4 MPa, and 356.4 MPa. Except for the density test results on type R bricks, all brick tests pass the American Society for Testing and Materials (ASTM C90, ASTM C129 and ASTM C55). This indicates that type T Eco-Bricks have effective workability.